Hubungan Kesehatan Mental dengan Motivasi Belajar Siswa - Badaruddin, Achmad; Erlamsyah, Erlamsyah; Said, Azrul (Konselor, 2016)
In motivation in study, mental health plays an important role. If someone has healthy mental health, the students will also be able to highly motivation in study. In fact there are students who still sickmental health as students are difficult to be expressive freely, self acceptance, self esteem and safety feeling that affect the motivation in study of students in terms of the studying preparation, learning proccess and follow up the study. This study aims to reveal how the image of mental health, student’s motivation in study and how the relationship between mental health and student’s motivation in study. This study used a descriptive quantitative approach correlational. Research conducted on the students of Madrasah Tsanawiyah Negeri Sintuk Toboh Gadang. The research findings revealed that 1) the emotional intelligence of students in middle category, 2) social interaction of students in middle category, 3) There is a significant and positive relationship between emotional intelligence and social interaction of students with the level of correlation is quite strong.